2000
DOI: 10.1080/713755898
|View full text |Cite
|
Sign up to set email alerts
|

The Rhyming Skills of Deaf Children Educated with Phonetically Augmented Speechreading

Abstract: Two experiments investigated whether profoundly deaf children's rhyming ability was determined by the linguistic input that they were exposed to in their early childhood. Children educated with Cued Speech (CS) were compared to other deaf children, educated orally or with sign language. In CS, speechreading is combined with manual cues that disambiguate it. The central hypothesis is that CS allows deaf children to develop accurate phonological representations, which, in turn, assist in the emergence of accurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0
4

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 84 publications
(32 citation statements)
references
References 38 publications
3
25
0
4
Order By: Relevance
“…The absence of left hemisphere superiority in deaf CS users is striking for two reasons. First, these subjects achieved a high level of rhyming, as attested by their high performance on the paper-andpencil control task in the present study, as well as by previous reports of good rhyming abilities in deaf CS users (Charlier & Leybaert, 2000;La Sasso et al, in press). Second, studies performed in normally hearing subjects using PET (De emonet et al, 1992(De emonet et al, , 1994 or fMRI (Fiez, 1997) have shown that phonological tasks induce strongly lateralised responses within the predominant hemisphere, within the cortical regions located around the Sylvian fissure, while the semantic component of word semantic judgment tasks is known to induce more bilateralised responses.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The absence of left hemisphere superiority in deaf CS users is striking for two reasons. First, these subjects achieved a high level of rhyming, as attested by their high performance on the paper-andpencil control task in the present study, as well as by previous reports of good rhyming abilities in deaf CS users (Charlier & Leybaert, 2000;La Sasso et al, in press). Second, studies performed in normally hearing subjects using PET (De emonet et al, 1992(De emonet et al, , 1994 or fMRI (Fiez, 1997) have shown that phonological tasks induce strongly lateralised responses within the predominant hemisphere, within the cortical regions located around the Sylvian fissure, while the semantic component of word semantic judgment tasks is known to induce more bilateralised responses.…”
Section: Discussionsupporting
confidence: 87%
“…However, phonological information contained in visual speech reading is poorer, scarcer, and less precise than information based on auditory inputs for hearing people because many phonemes have similar labial images or no labial correlates. Deaf children exposed to CS early and intensively, who constitute a minority among the deaf community, constitute an exceptional case, in that they acquire a rich and precise phonological system, allowing them to perform accurately rhyming tasks (Charlier & Leybaert, 2000;La Sasso, Crain, & Leybaert, in press).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…school children, and showing that CS-home children reached greater accuracy in rhyming tasks than CS-school, SL-home, and SL-school children (Charlier & Leybaert, 2000;Leybaert, 2000). We also predicted that the effect of grapheme dominance would be intermediate in the CS-school groups and lower in SL groups.…”
mentioning
confidence: 83%
“…& Daisey, 1992, andCharlier &Leybaert, 2000 for more complete descriptions of CS in English and in French, respectively, and Messing, 1999, for a discussion of the differences between CS and sign language [SL]). Children who have been exposed to CS early and intensively at home (i.e., CS-home children) develop a spelling production system strongly guided by phonology.…”
mentioning
confidence: 99%